Development of the E-Posyandu Kelor Gateway Based on the Continuum of Care - Rachmawati, Ervina; Puspitasari, Trismayanti Dwi; Santi, Maya Weka; Yunus, Muhammad (P3M Politeknik Negeri Jember, 2025)
The maternal mortality rate (MMR), infant mortality rate (IMR), and stunting rate in the Jember regency have not reached the standards set by the government. Efforts to reduce made through early detection of risk factors using the continuum of care model at to develop an e-Posyandu system. The purpose of this study was to develop an e-Posyandu information system into a “Kelor Gateway e-Posyandu” information system based on the continuum of care and equipped with a reminder system. This was a research and development study. The sample were 15 cadres from integrated service posts Manggis 15, 15A, and 18. The system was developed using the waterfall method. The results showed that the system’s development e-Posyandu based on the continuum of care reports could be automatically recapitulated and adjusted according to the manual report. This means that the cadres could send the health data reports as soft copies (PDF) or hard copies (print) to the midwives. The Kelor Gateway e-Posyandu was also equipped with a reminder system to send the integrated service posts’ acitivity schedules via SMS to pregnant women and mothers. This system has been implemented by the research subjects at their integrated service posts. and the system has facilitated the early detection of MMR, IMR, and stunting. For future studies, the Kelor Gateway e-Posyandu needs to be implemented simultaneously at all integrated service posts in the Kemuning Lor village.